"Why can't I take a full-shot of myself? Of course I can!" Studying selfies as socio-technological affective practices - Hynna-Granberg Kaisu (Routledge Journals. Taylor & Francis, 2022)
This article studies selfie-production as a socio-technological affective practice, bringing attention to a new and largely unstudied type of selfies, private selfies. Discussing an example of five Finnish women's experiences with a body positive #righttobeseen campaign, the article argues for selfie scholarship to move beyond analyses of representation and image-sharing on social media platforms, if it is to understand selfies' diverse role in selfie-takers' lives. The article offers an analytical schema for studying selfies as socio-technological affective practices, combining the method of interview studies with affect theory and examination of selfies' socio-technological underpinnings.